Neurological complications of coronary arteriography - Mutarelli, Eduardo Genaro; Arie, Siguemituzo; Alóe, Flávio; Scaff, Milberto (São Paulo Medical Journal, 1994)
The authors report a 46 year-old female who was submitted to a right femoral artery coronary arteriography. During the procedure she presented an upward, downward and convergence gaze paresis; an upbeating nystagmus. A NMRI showed a change in T-2 weighted signal of the left paramedian mesencephalic region. A diagnosis of stroke was made and dextran 40 was prescribed. Vertical gaze paresis progressively disappeared. Convergence paresis and nystagmus improved partially only. The possible pathophysiological basis underlying this clinical picture are: catheter-induced dislodgement of an atheromatous plaque; small thrombi formation and release from the catheter tip; catheter-induced vascular lesion with subsequent thromboembolism or dissection of the intima; cardiac arrhythmia; catheter-induced or contrast medium-induced arterial spasm; a combination of two or more of these.